Effect of traditional medicinal plants on the pathogenic potential of the versatile pathogen Staphylococcus aureus - Shil, Aparna; Shuvo, Md Nazmussakib; Sultana, Habiba; Alam, Nuhu; Himel, Mahbubul Kabir (Jahangirnagar University Journal of Biological Sciences, 2024)
This study explores the effects of Neem (Azadirachta indica) and Papaya (Carica papaya) leaf extracts on the pathogenicity of Staphylococcus aureus. Through in vitro assays, we investigated the impact of these medicinal plant extracts on bacterial metabolic activity and pathogenic factors. Results indicate that the growth of Staphylococcus aureus was differentially decreased by the plant extracts, with Neem demonstrating a greater reduction compared to Papaya. Moreover, both Neem and Papaya extracts, either alone or in combination, significantly inhibited bacterial biofilm formation, with reductions of 39%, 48%, and 7%, respectively. Both aqueous and ethanolic extracts exhibited inhibitory effects on bacterial growth, with ethanolic extract showing stronger potency. However, the extracts did not influence the bacteria's haemolytic characteristics. Overall, these findings suggest that traditional medicinal plant extracts possess potential in mitigating S. aureus pathogenicity, however, further mechanistic investigations are warranted to elucidate underlying mechanisms. Jahangirnagar University J. Biol. Sci. 12(1 & 2): 73-86, 2023 (June & December)